Plano de la ciudad de Iquitos - (:unkn) unknown (My University, 1920)
The map shows the detailed graphic representation of the territory of the city of Iquitos, providing visual information on the distribution of streets, avenues, rivers (Amazon, Nanay and Morona Cocha Lake) and other significant elements.

El Plano muestra la representación gráfica y detallada del territorio de la ciudad de Iquitos proporcionando información visual sobre la distribución de calles, avenidas, ríos (Amazonas, Nanay y Lago Morona Cocha) y otros elementos significativos.
Map of the city of Iquitos
Keywords: El mapa incluye anuncios de distintas empresas y entidades de toda la zona.; Iquitos (Peru)--maps; Peru--cartographic materials; Peru--maps